Pengenalan dan Implementasi Metode Six Sigma pada Program Studi Teknik Industri, Fakultas Rekayasa Sistem, Universitas Teknologi Sumbawa - Didik Setiyadi; Saludin Saludin; Rully Pramudita; Nada Aura Wansa; Restu Amalia Novita (Jurnal Pengabdian Pada Masyarakat, 2021)
INTRODUCTION AND IMPLEMENTATION OF SIX SIGMA METHODS IN INDUSTRIAL ENGINEERING STUDY PROGRAM, FACULTY OF SYSTEMS ENGINEERING, SUMBAWA UNIVERSITY OF TECHNOLOGY. In implementing the six sigma method in carrying out organizational activities with the aim of improving business performance through the introduction of the stages of the six sigma methodology; namely, initializing a six sigma project through the define stage, defining and measuring variables through the measure stage, analyzing the variables that affect CTQ through the analyze stage, conducting further variable testing and optimizing variables that affect CTQ through the improve stage, and performing control to stabilize the implementation of the results of the improve stages on a regular basis through the control stages, so that participants can train themselves and immediately practice the implementation of six sigma projects for simple cases that are often encountered in the environment around the Sumbawa University of Technology. Participants who registered in the activity were students of the Industrial Engineering study program as many as 128 participants, where from the results of the search for feedback on this activity, 75 participants were carried out via google form. The results of the feedback from this PkM activity with 10 questionnaire questions with a scale of very good (4), good (3), sufficient (2) and less (1) overall that stated very good as many as 44%, good 49%, quite 7 % and less 0%.